lndicators of homosexuality in the Human Figure Test: comparison between homosexual and heterosexual men - Fernández Dávila, Percy (2003)
This study reviews graphic indicators (GI) of homosexuality in the Human Figure Drawing Test (HFDT) which have been described in various texts on projective tests. 36 homosexual and 30 heterosexual men were enrolled, all middle-class and aged 18-50. Each participan! drew three figures (man, woman and themselves). Information from the literature, the Gis from the study, and the expertise of a group of psychologists concerning which Gis describe homosexuality in HFDTs were analyzed. Results show that large differences do not exist between Gis of drawings by homosexual men and heterosexual men. However, three characteristic indicators were found in the drawings of homosexual men (Semi-Nude Female and Self Figures, Female Figure with Cupid Arch Mouth, and Self Figure with Large/ Emphasized Eyes) and one indicator in those by heterosexual males (Male Figure with Empty Eyes). Almost al! of the Gis found in the literature fail to describe homosexuality and that clinicians continue to be influenced by stereotypic conceptions of homosexuality.